The Effect of Profitability and Leverage on Firm Value with Firm Size as a Moderating Variable - Panjaitan, Ida Veronika; Supriyati, Diana (SAN Scientific, 2023)
This study aims to empirically prove and test the effect of profitability and leverage on firm value, with firm size as a moderating variable in food and beverage companies listed on the Indonesia Stock Exchange (IDX) 2019-2021. This quantitative study uses a purposive sampling method with a sample of 23 firms. The data used in this research is secondary data. The results of this study indicate that (1) Profitability negatively affects firm value. (2) Leverage has a positive effect on firm value. (3) With moderation, firm size can moderate profitability with a positive relationship (strengthen) to firm value. (4) Firm size can moderate the relationship of negative (weakened) leverage to firm value. The implications of this study for a firm to consider the factors of firm size, leverage, and profitability, and can be used as a reference by other companies in business strategy, understand aspects of the industry they are in, and pay more attention to environmental developments that can affect the firm's business so that it can increase firm value.